Kajian Fiqih Muamalah Dalam Memahami Konsep Transaksi Mukhabarah Pada Mata Kuliah Fiqih Program Studi Pendidikan Guru Madrasah Ibtidaiyah - Karimah, Zianatul; Wahyuni, Siti (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
This study contains a study of fiqh muamalah in the realm of mukhabarah for semester III students of the Elementary Madrasah Teacher Education Program. The purpose of this study is to explain the relationship between the fiqh muamalah course on the concept of mukhabarah transactions with the education program as an elementary madrasah teacher. The results of the study came from participant interviews, namely semester III students of the PGMI class, the Faculty of Tarbiyah, also from observations on learning the fiqh course in the class. The data analysis technique used was content analysis. From the results of the data collection above, it can be concluded that the fiqh muamalah course in the discussion of mukahabarah has many connections with the education of an elementary madrasah teacher, starting from the formation of pedagogical competence, learning basic life sciences in socializing with students, and cooperative relationships with everyone involved in the teaching and learning process.